Critical assumption planning: A practical tool for managing business development risk - Sykes, Hollister B.; Dunham, David (Journal of Business Venturing, 1995)
Although much has been written about the practice of new business development, the authors continue to find corporate managers and entrepreneurs repeating the same mistakes and often reaching the conclusion that venturing in the corporate environment won't work. The problem stems from a mental model about how business should be managed and managers' performance assessed. Corporate managers of existing businesses are judged against meeting plan. In growing new businesses, however, strict adherence to “the plan” can lead to business failure. To manage business development risk, venture managers must learn to deal with uncertainty. Whereas managers of mature businesses practice the ethic of predictability, venture managers must follow a learning ethic. Working with Fortune 100 corporations, the authors have evolved a practical, disciplined process for business development risk management that focuses on learning. Titled critical assumption planning (CAP), the process maximizes learning about new markets at lowest cost. Major uncertainties in the business proposition are isolated as critical planning assumptions. Critical assumptions in the plan are then tested. The test sequence is determined by the potential reduction of uncertainty per dollar of test cost. Assessment of the assumption test results marks a milestone. At each milestone the business plan is revised to reflect what has been learned, and the venture is redirected or terminated. This process avoids the wasted effort and expense of pursuing the original plan until commercial failure becomes obvious. The key steps in this learning process are identification of critical assumptions and cost-effective testing of assumptions. Because these steps are unfamiliar to most corporate managers, effective use requires a new perspective and new planning tools. The study explains this perspective and introduces new tools for employing the process. Following are some planning innovations that have been effective in changing perspective and that also are of practical use: 1.1. Differentiation between primary and derivative assumptions with focus on extracting and understanding the primary assumptions.2.2. Early construction of a model of the business plan that allows calculation of the impact of primary assumptions such as price or sales productivity factors on derivative assumptions such as revenues and income.3.3. Assignment of uncertainty ranges to the primary assumption values, not just the most likely values.4.4. Identification of the critical planning assumptions by determining the impact of their uncertainty ranges on venture net present value.5.5. Selection of the next venture milestone based on the test program that results in maximum reduction of uncertainty at least cost in least time for the most critical assumption(s). Using CAP, managers can control risk despite the many uncertainties surrounding a new business proposition. Above all, decisions to stop or redirect ventures can be taken earlier, saving the corporation money and venture managers their career credibility.